Transforming India : social and political dynamics of democracy - Frankel, Francine R. (New Delhi ; New York : Oxford University Press, 2000)
Revision of papers originally presented at a conference held at India International Centre in Nov. 1997.
Keywords: Democracy -- India -- Congresses; India -- Politics and government -- 1947- -- Congresses